UMP, HKA establish international collaboration in Dual Degree in Electrical Engineering Electronics - Mohd Ruzaimi, Mat Rejab (2022)
GERMANY, 31 May 2022 - Universiti Malaysia Pahang (UMP) signed a partnership with Hochshcule Karlsruhe (HKA) Germany to carry out the UMP-HKA Dual Degree in Electrical Engineering (Electronics) programme.